A pure mucocele-like lesion of the breast diagnosed on ultrasonography-guided core-needle biopsy: is imaging follow-up sufficient? - Yun Joo Park; Eun-Kyung Kim (Ultrasonography, 2015)
Purpose: To evaluate the upgrade rate of ultrasonography (US)-guided core-needle biopsy (CNB) of the breast for a pure mucocele-like lesion (MLL), to evaluate the clinical and radiologic features, and to correlate the image-pathologic features further on to guide the management of MLL. Methods: Between January 2003 and February 2013, 14-gauge US-guided CNB was performed in 18,111 cases. Thirty-two cases associated with MLL were identified, and five cases of MLLs associated with breast carcinoma or with other high-risk breast lesions (i.e., atypical ductal hyperplasia [ADH], papillary lesions, lobular carcinoma in situ, and radial scar complex) were excluded. Among these 27 pure MLLs, 21 cases with surgical or vacuum-assisted excision (VAE) pathology were included in our study. Medical records, mammograms, and ultrasonograms were reviewed for the clinical and radiologic features of the cases. Results: Among the 21 cases with pure MLLs at CNB, the final pathology showed a 0% proportion of cases upgraded to malignancy. All the 21 cases with either surgical or VAE pathology were benign MLLs including three cases of focal involvement of ADH (14.3%). The common features were mammographic features of microcalcifications that were round in shape and had a grouped distribution. The US features included oval shape, circumscribed margin, parallel orientation, complex solid and cystic echo pattern, no posterior feature, and complex solid and cystic echoic masses. The predominant Breast Imaging Reporting and Data System (BIRADS) category was 4A. All the lesions showed image-pathologic concordance. Conclusion: For pure MLL on US-guided CNB with image-pathologic concordance, close imaging follow-up might be considered instead of surgical excision.